Increased PD-1 expression in livers associated with PD-1-antibody-induced hepatotoxicity - Miro Saarela; Essi Parviainen; Ana Lleo; Luca di Tommaso; Hanna Raunio; Krista Kankaanranta; Katri Vuopala; Aino Rönkä; Sini Nurmenniemi; Raija Kallio; Arja Jukkola; Katri S. Selander (BMC Immunology)
Abstract Vanishing bile duct syndrome (VBDS) is a serious drug induced liver injury characterized by chronic cholestasis and loss of intrahepatic bile ducts. VBDS has been reported also following checkpoint inhibitor treatment. We compared CD3 + , CD4 + , CD8 + , CD20 + , CD57 + , PD-1 + and PD-L1 + lymphocyte infiltrates in liver biopsies of patients that encountered VBDS (n = 2) or hepatotoxicity (n = 3) after pembrolizumab (n = 4) or nivolumab (n = 1) treatment with samples from normal liver (n = 10), non-alcohol steatohepatitis (NASH, n = 10), primary biliary cholangitis (PBC, n = 10) or pembrolizumab-treated patients without adverse events (n = 2). Notably, none of the cancer patients had primary nor metastatic liver tumors. We also studied direct growth effects of pembrolizumab on primary human intrahepatic biliary epithelial cells (HIBEpiC) in vitro. Liver sections of all checkpoint inhibitor- treated patients exhibited significantly higher CD3 + infiltration than normal livers, and significantly higher PD-L1 + , CD4 + and CD8 + infiltration, than other groups. PD-1 + infiltration was significantly increased in livers of patients with severe hepatic adverse event. CD57 + infiltration was similar in normal livers, NASH- and PBC groups, but highly increased in the checkpoint inhibitor-treated patients. Immune cell infiltrates were similar between NASH and normal livers. PBC samples had significantly higher CD3 + , CD4 + , CD8 + and CD20 + infiltrates than normal livers. HIBEpiC express PD-L1 but pembrolizumab did not affect their viability in vitro. Our findings suggest that VBDS is not due to direct cytotoxicity of checkpoint inhibitors and that the immunological attack against livers induced by these drugs is different from other cholestatic liver conditions. Biological insight: Checkpoint inhibitors upregulate PD-1 and PD-L1, as well as cytotoxic CD57 + cells in the non-cancerous liver tissues and this may be associated with checkpoint inhibitor-induced hepatotoxicity.